Bashkirian Rugosa (Anthozoa) from the Donets Basin (Ukraine). Part 10. The Family Krynkaphyllidae fam. nov. - Fedorowski, Jerzy (Acta Geologica Polonica)
The known occurrence of corals distinguished here in the new Family Krynkaphyllidae varies at the subfamily level. Those of the Subfamily Krynkaphyllinae subfam. nov. are so far almost unknown from outside of the Donets Basin. In contrast, those of the Subfamily Colligophyllinae subfam. nov. are common, possibly ranging from the lower Viséan Dorlodotia Salée, 1920, a potential ancestor of the family, to the Artinskian Lytvophyllum tschernovi Soshkina, 1925. They bear different generic names, but were all originally described as fasciculate colonial. A detailed study of Lytvophyllum dobroljubovae Vassilyuk, 1960, the type species of Colligophyllum gen. nov., challenges that recognition in that at least some of those taxa are solitary and gregarious and/or protocolonial. As such, solitary, protocolonial and, probably, fasciculate colonial habits are accepted in the Colligophyllinae subfam. nov., whereas the Krynkaphyllinae subfam. nov. contains only solitary taxa. The resemblance to the Suborder Lonsdaleiina Spasskiy, 1974 led to the analysis of families included in that suborder by Hill (1981) in the context of their relationship, or homeomorphy, to Krynkaphyllidae fam. nov. This question primarily concerns the Family Petalaxidae Fomichev, 1953; a relationship with the Family Geyerophyllidae Minato, 1955, is more distant, if one exists. The distinct, parallel stratigraphic successions of taxa within two subfamilies of the Krynkaphyllidae fam. nov. document their probably common roots and early divergence. However, a lack of robust data precludes an interpretation or treatment of those successions as phylogenetic. The absence of key stratigraphic and morphologic data meant that eastern Asiatic taxa have not been considered in these successions; however, morphological similarities allow for their tentative inclusion within the Krynkaphyllidae fam. nov. The following new taxa are introduced: Krynkaphyllidae fam. nov., Krynkaphyllinae subfam. nov., Colligophyllinae subfam. nov., Krynkaphyllum gen. nov., Colligophyllum gen. nov., Protokionophyllum feninoense sp. nov., Krynkaphyllum multiplexum sp. nov., Krynkaphyllum validum sp. nov., and three species of Protokionophyllum Vassilyuk in Aizenverg et al., 1983 left in open nomenclature.
Keywords: Rugosa (Anthozoa); taxonomy; Relationships; Bashkirian; Donets Basin